A Discussion of Richard Flacks and Nelson Lichtenstein's The Port Huron Statement: Sources and Legacies of the New Left's Founding Manifesto. Issue 3 (31st August 2016) - Blitz, Mark
Abstract : The Port Huron Statement was one of the most important manifestos of the New Left in the United States. A foundational statement of the theme of "participatory democracy, " the text had an important influence on post-1960s politics and, arguably, on post-1960s political science. The recent publication of a new edition of the Statement is an occasion for reflection on its importance. And so we have invited a distinguished cast of political scientists shaped by the events of the sixties to comment on the impact of the Statement on their own way of envisioning and practicing political science.